Brand Management : Principles and applications for effective branding - Singh, Jaywant; Shukla, Paurav (Kogan Page Limited, 2024)
Learn how to build, develop and manage brands with this applied textbook which also explores the latest developments in digital branding, brand crisis and brands' responsibility